A tribological perspective on friction and performance in Olympic snow and ice sports - Almqvist, A.; Kalliorinne, K.; Supej, M.; Sjödahl, M.; Holmberg, H.-C. (Sport Sciences for Health, 2025)
With 62% of medals at the upcoming 2026 Winter Olympics in Milano-Cortina to be awarded in skiing disciplines and the remaining 38% in ice-based events, understanding the determinants of performance is critical. Despite extensive examination of athletes` physiological, biomechanical, and psychological attributes, the role of tribology—particularly in understanding friction on snow and ice—has received less attention. This is a scientific perspective article outlining key tribological factors and highlighting their importance in Olympic winter sports. In skiing, optimising the ski-snow interaction requires a comprehensive understanding of how friction is influenced by snow crystal morphology, temperature, ski base material and structure, ski stiffness, skier technique, and environmental conditions. For ice-based events, friction is determined by a combination of ice surface roughness, temperature, and sport-specific preparation techniques, as well as equipment design (e.g. blade material and geometry, the running surface finish of curling stones) and athlete technique (e.g. angle of attack in speed skating, sweeping in curling). Ice preparation techniques further influence friction, with specific conditions tailored to each sport. In conclusion, advancements in Olympic winter sports have been significant. However, future breakthroughs in performance may lie in applying tribological insights to optimise the complex interactions between athletes, equipment, and the unique properties of snow and ice. This perspective article aims to guide future research by synthesising current understanding and identifying emerging challenges in winter sports tribology.